Improvement of the budgeting system of IT projects - Dalyk Volodymyr; Zapisotskyi Ivan; Ilchyshyn Mykola; Matviievskyi, Nazar (Global Prosperity, 2024)
Improving the budgeting system for IT projects is a pressing issue in the modern business environment, where high competition and rapid technological changes demand effective management of costs and resources. The purpose of this research is to enhance the budgeting system to ensure efficient project management. To achieve this goal, an analysis of current approaches to IT project budgeting was conducted, identifying problems in existing systems and outlining the main principles for improvement. One of the key principles for improvement is ensuring transparency and accountability in budgetary processes. This involves clearly defining expenses and controlling their use. Additionally, flexibility and adaptability of the system are crucial, allowing for adjustments in project conditions and quick responses to changes. For enhancing the budgeting system, it is recommended to implement Agile and Scrum approaches, which enable iterative budget development and involve the team in the planning process. It is also important to consider the risks and uncertainties associated with IT projects and use stochastic modeling methods for their forecasting. It is anticipated that improving the budgeting system will contribute to more effective IT project management and provide more accurate financial resource planning.